2012
DOI: 10.1016/j.mrgentox.2011.09.013
|View full text |Cite
|
Sign up to set email alerts
|

In vitro genotoxicity testing strategy for nanomaterials and the adaptation of current OECD guidelines

Abstract: Highlights► We consider current in vitro OECD genotoxicity tests for nanomaterials. ► Ames test does not appear to be suitable for nanomaterial assessment. ► In vitro HPRT and micronucleus assays require nanomaterial specific protocols. ► We recommend a strategic in vitro genotoxicity testing strategy for nanomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
192
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(203 citation statements)
references
References 81 publications
5
192
0
Order By: Relevance
“…However, more in vivo studies are required to fully understand the mechanism of TiO 2 nanoparticles toxicity. Likewise, more caution should be considered for toxicity assessment of nanoparticles because of the limitations and potential artifacts of the results (Doak, et al, 2012, Landsiedel et al, 2009. This study provides a better insight into the potential toxicity of nanoparticles with respect to their physiochemical characteristics.…”
Section: Most Of the Toxicological Results On Nps Have Been Generatedmentioning
confidence: 92%
“…However, more in vivo studies are required to fully understand the mechanism of TiO 2 nanoparticles toxicity. Likewise, more caution should be considered for toxicity assessment of nanoparticles because of the limitations and potential artifacts of the results (Doak, et al, 2012, Landsiedel et al, 2009. This study provides a better insight into the potential toxicity of nanoparticles with respect to their physiochemical characteristics.…”
Section: Most Of the Toxicological Results On Nps Have Been Generatedmentioning
confidence: 92%
“…Expressing the concentration in terms of mass/volume is the easiest option, but is however not always the most relevant 105 . Which was pointed out in a review by Johnston et Subsequently attention should go to standardisation of nanotoxicity methods in terms of incubation conditions like NP concentration and incubation time as overexposure conditions should be avoided 113 . The importance of avoiding overexposure conditions becomes clear when evaluating genotoxicity for example, as acute toxicity at overexposure levels can mistakenly be interpreted for genotoxicity since apoptosis itself induces DNA fragmentation 114,115 .…”
Section: Issues With Routine In Vitro Methodsmentioning
confidence: 99%
“…Relatively low toxicity has been found even when nanoparticle concentrations as high as 100 μg/mL were used, yet some studies have reported some level of damage to cells. 82,83 Basically, in vitro experiments have demonstrated the toxicity of SPIONs, causing cellular stress, [84][85][86][87][88] alterations in gene expression due to chromatin changes and genotoxicity, 82,89,90 decrease in cell proliferation, 83,85,87,88 and promotion of a proinflammatory environment. [91][92][93] In most studies, SPIONs do not exert any reported effects on adipogenic 94,95 and neurogenic differentiation.…”
mentioning
confidence: 99%